THE HISTOLOGY AND HISTOMORPHOMETRY OF ETAWAH CROSSBREED SPLEEN - Yanti, Tri Ulfah Arema; Suwiti, Ni Ketut; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2019)
The objective of this study to find out the histological and histomorphometry description of etawah crossbreed (PE) spleen. The spleens were collected from 10 male and female PE goats in Kampung Jawa slaughterhouse, Denpasar, Bali, then fixed in a solution of 10% Neutral Buffer Formalin processed for making preparation histology based on the method of Kiernan with hematoxylin-Eosin (HE) staining techniques. The goat's spleen consists of capsule, white and red pulp. Spleen histomorphometry of male and female PE goats obtained results, each having a capsule thickness of 128.58 ± 0.37 µm and 163.40 ± 0.35 ?m, trabecula thickness of 125.68 ± 0.13 µm and 131.45 ± 0, 28 µm, and white pulp diameter 466.63 ± 0.15 µm and 392.40 ± 0.30 µm respectively. It was concluded that gender affected the histology structure and histomorphometry of etawah crossbreed spleen.